The 46-kilodalton-hemolysin gene from Treponema denticola encodes a novel hemolysin homologous to aminotransferases. - Chu, L (1995)
The 46-kDa hemolysin produced by Treponema denticola may be involved in the etiology of periodontitis. In order to initiate a genetic analysis of the role of this protein in disease, its gene has been cloned. Synthetic oligonucleotides, designed on the basis of the previously reported amino-terminal amino acid sequence of the 45-kDa hemolysin, were used as primers in a PCR to amplify part of the hemolysin (hly) gene. This PCR product was then used to clone the entire hly gene from libraries of T. denticola genomic DNA. Constructs containing the entire cloned region on plasmids in Escherichia coli produced both hemolysis and hemoxidation activities either on sheep blood agar plates or in liquid assays. Sodium dodecyl sulfate-polyacrylamide gel electrophoresis and Western blot (immunoblot) analysis revealed that the constructs synthesized a protein with molecular size of about 46 kDa which was reactive with anti-T. denticola hemolysin. Nucleotide sequence analysis indicated that the largest open reading frame could encode a protein with a calculated molecular size of 46.2 kDa. The first 31 amino acids encoded by this open reading frame were identical to the experimentally determined amino-terminal sequence of the 45-kDa hemolysin. These results indicate that the entire hly gene has been cloned. The deduced amino acid sequence of the T. denticola hly gene is homologous (23 to 37% identity) to those of proteins that are members of a family of pyridoxal-phosphate-dependent aminotransferases. This suggests that the 46-kDa hemolysin may be related to an aminotransferase and have a novel mechanism of hemolysis. However, the functional aspects of this relationship remain to be investigated.